Differentially Painting Human Chromosome Arms with Combined Binary Ratio-labeling Fluorescence In Situ Hybridization - Wiegant, Joop; Bezrookove, Vladimir; Rosenberg, Carla; Tanke, Hans J.; Raap, Anton K.; Zhang, Hongen; Bittner, Michael; Trent, Jeffrey M.; Meltzer, Paul

(untitled) (Genome Research, 2000)
Recently we developed a novel strategy for differentially painting all 24 human chromosomes. It is termed COBRA–FISH, short for combined binary ratio labeling–fluorescence in situ hybridization. COBRA–FISH is distinct from the pure combinatorial approach in that only 4 instead of 5 fluorophores are needed to achieve color discrimination of 24 targets. Furthermore, multiplicity can be increased to 48 by introduction of a fifth fluorophore. Here we show that color identification by COBRA–FISH of all of the p and q arms of human chromosomes is feasible, and we apply the technique for detecting and elucidating intra- and interchromosomal rearrangements. Compared with 24-color whole chromosome painting FISH, PQ-COBRA–FISH considerably enhances the ability to determine the composition of rearranged chromosomes as demonstrated by the identification of pericentric inversions and isochromosomes as well as the elucidation of the arm identity of chromosomal material involved in complex translocations that occur in solid tumors.